Correlation of the structure of the transmembrane domain of the neu oncogene-encoded p185 protein with its function. - Brandt-Rauf, P W (1990)
The human homologue of the neu oncogene is frequently found in human tumors. Certain amino acid substitutions at position 664 in the transmembrane domain of the neu oncogene-encoded p185 protein product are known to cause malignant transformation of cells. Using conformational energy analysis based on ECEPP (empirical conformational energies for polypeptides program), we have previously determined the preferred three-dimensional structures for the transmembrane domain of the p185 protein with a transforming (glutamic acid) and a nontransforming (valine) substitution at the critical position 664 and found that the global minimum-energy conformation of this region in the nontransforming protein contains a sharp bend, whereas the global minimum-energy conformation for this region from the transforming protein is entirely alpha-helical. We now demonstrate that this result holds for other known nontransforming (glycine, histidine, tyrosine, and lysine) and transforming (glutamine) substitutions at position 664. Furthermore, a simple statistical thermodynamic analysis of the results indicates that approximately 85% of each of the nontransforming sequences exist with the bend at positions 664 and 665, while approximately 90% of each of the transforming sequences exist as an alpha-helix. About 9% of the nontransforming sequences exist as the alpha-helix. These results suggest that if the intracellular concentration of the normal protein is increased at least 10-fold, thereby increasing the alpha-helical form by this factor, cell transformation should result. This conclusion is directly supported by genetic experiments in which this level of overexpression of the normal protein was achieved with attendant cell transformation.